Abortion in Islamic Jurisprudence - A Mohsenni (JRI, 2005)
From medical point of view, abortion is the expulsion of partially formed fetus or abortion of an incomplete pregnancy by the mother or another person. In Islamic religious beliefs, fetus is regarded as two forms: fetus with soul and human life and fetus without any soul. On prohibition of abortion in the first case, there is no difference between Shiites and Sunnites, as fetus in this case has self or soul and based on all the versus and traditions of Islam, its abortion is counted as murdering a human. In the second case, some Sunnites allow its abortion but Shiites prohibit this one too, of course aside from some exceptions. This paper tries to dis-cuss two important issues on abortion; the first one is the soul inspiration of the fetus. In this regard some medical doctors believe that there is not such a thing as lifeless fetuses and even some believe that even spermatozoids and ova have life before conception. Some others believe that fetus has movements long be-fore its movements are detected by the mother and this is due to the tininess of the fetus and largeness of the fetal sac, but upon the growth of the fetus its movements are perceived. It is to be said that we have to accept all the sensory issues that are proven by medicine without any question. But it should be noted that Islamic jurisprudents do not solely mean life, but human life which is made of the inspiration of life into the body. Life has different types in ancient philosophers’ opinion: Vegetative, animal and human. Vegetative life is in need of food, respiration, temperature, and … Animal life is in need of the senses and voluntary movements, aside from the previously mentioned ones. Human life has the ability of intuition in addition to the senses, movement, etc and this capability is due to the effects of his abstract rational soul. Nowadays, scientific evi-dence has been added to rational and religious reasons for the existence or being of humans too. From medical point of view, there are other classifications for life and its stages, but there is not much expectation from medical science to comprehend the state of possession of soul by fetus. Science penetrates in the sen-sory world but has no other choice except resorting to silence in the worlds of philosophy and religion. Materialists have made a mistake for stepping out of the boundaries of science by denying the injunctions of rationality and philosophy; as there is no conflict between physical and spiritual causes, although some theo-logians have made mistakes on this issue too. The human soul is disengaged or isolated from matter and its appendages like time and place; but as a contingent being it is finite and has essence, contrary to the exis-tence of God which is immaterial and has no essence. Soul does not incarnate into the body and does not have a specific place in it, nor does it mount on it. Soul is the expedient of the body and has expediential affinity to it, but the truth of this affinity is not philosophically, religiously or scientifically known. From this expedient belonging of soul to body, life is blown into the body and this inspiration of life into the body is called life. This is not the blownability of soul but blowability by soul, therefore the meaning of blow-nability is life. Though life appears in the fetus after 4 months of pregnancy, but its exact day and time is not known. In the second part of the paper, abortion is studied on the following premises: In the premise that there is certitude for the death of the fetus, in the premise that fetus lives on but it will end in the mothers death or the premise that it will harm the health of the mother, the assumption that the birth of the fetus will cause severe hardship for the mother, in the case of hydatidiform mole and abortion in the case of illegitimacy.
Keywords: Abortion, Science, Islamic jurisprudence, Shiites and Sunnites, Prohibition, Vegetative, Animal and human life, Soul inspiration, Hardship